Synergistic Enhancement of Anti-aging and Fatigue Properties of Graphene/Rubber Powder Composite Modified Asphalt - Yunpeng SHANG (Medžiagotyra)
Traditional modified asphalt has limitations in anti-aging, fatigue resistance, and environmental protection performance. In this study, a new type of graphene/rubber powder composite modified asphalt (CMA) is prepared to synergistically enhance the anti-aging and anti-fatigue properties. CMA is prepared by melting and co-mixing at 180 ℃ and high-speed shearing at 5000 rpm. The performance is evaluated using scanning electron microscopy (SEM), dynamic shear rheometer (DSR), and Fourier transform infrared spectroscopy (FTIR) in the experiment. The results showed that the modified asphalt showed excellent anti-aging performance. After 60 hours of aging, the phase angle only decreased from 60.1° to 56.4°, while the phase angle of the unmodified matrix asphalt group decreased from 50.1° to 40.3°. The smaller the decrease of phase angle, the better the aging resistance of asphalt. The anti-aging performance of the modified asphalt was about 62.2% higher than that of the base asphalt. The aging index of carbonyl and sulfoxide groups significantly decreased (0.035 and 0.037, respectively). The anti-fatigue performance has also been significantly improved, with the CMA reaching 113,652 cycles at 2.5 % strain, an increase of 73.98 % compared to the matrix asphalt group. This mechanism was attributed to the layered barrier structure of graphene (delaying oxidation) and the sulfur crosslinked network of rubber powder (absorbing thermal stress). At the same time, the rigid structure of graphene combined with the flexibility of rubber formed an interlocking network that resisted crack propagation and could suppress the propagation of asphalt microcracks. Such a structure can effectively improve the anti-aging and anti-fatigue performance of modified asphalt, providing a promising solution for the design of long-life pavement, especially in heavy traffic and extreme climate environment.